Impaired inactivation by antithrombin and hirudin and preserved fibrinogen-clotting activity of thrombin in complex with antithrombin antibody from a patient with antiphospholipid syndrome - Kolev, Krasimir; Léránt, István; Skopál, Judit; Kelemen, Anna; Nagy, Zoltán; Machovich, Raymund (Thrombosis and Haemostasis, 2005)
Immunoglobulin G (IgG) isolated from the blood plasma of a patient with secondary antiphospholipid syndrome (APS) expresses fibrinogen-clotting and amidolytic activity (the thrombin activity in 20 μmole IgG is equivalent to approximately 5 nmole pure thrombin), and activates factor XIII. Hirudin (1 μM) decreases the intrinsic thrombin activity of the APS IgG by only 25%, whereas it inhibits completely pure thrombin with equivalent activity. Under conditions, when antithrombin inactivates 60% of the thrombin activity in the presence of normal IgG, the APS IgG protects almost completely the added thrombin against inactivation by antithrombin. Heparin, however, partially relieves this protective effect and at the same time it facilitates the inhibition of the intrinsic thrombin activity by antithrombin. The APS IgG reduces the thrombin activity in protein C activation assay by 50% compared to the activity in the presence of normal IgG. All described properties are related to the Fab fragment of the antibody. The IgG preserving the fibrin-generating activity of thrombin with concomitant protection against inhibitors unravels a new aspect of the thrombotic mechanism in APS. This condition is probably rare: only one out of 23 examined patients with primary or secondary APS expresses IgG with the described properties.
Keywords: Antiphospholipid syndrome; thrombin; antithrombin; hirudin; protein C